1978
DOI: 10.1210/jcem-46-4-622
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol and Progesterone Concentrations in Myometrium of Pregnancy and Their Relationships to Concentrations in Peripheral Plasma*

Abstract: 17 beta-Estradiol (E2) and progesterone (P) concentrations in blood and in the myometrium of human pregnancy at term (n=33) and in a few samples (n=5) around midterm of pregnancy were determined. E2 concentration in the myometrium (per g wet wt) at midterm was lower than the concentration in the plasma (per ml) so that the myometrium to plasma (My:Pl) ratio was 0.7. Relative to plasma concentration, the myometrial E2 increased little from midterm to term so that My:Pl was only 0.2 at term. Although P concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…M during pregnancy (2,11). However, we did not observe any significant effect of E 2 on hOAT4 activity within a concentration range of 10 Ϫ8 -10 Ϫ5 M (Fig.…”
Section: ϫ7mentioning
confidence: 54%
“…M during pregnancy (2,11). However, we did not observe any significant effect of E 2 on hOAT4 activity within a concentration range of 10 Ϫ8 -10 Ϫ5 M (Fig.…”
Section: ϫ7mentioning
confidence: 54%
“…The plasma E 2 concentration during pregnancy increases steadily to around 0.8 ϫ 10 Ϫ7 M at term (3,20). At concentrations observed during pregnancy (10 Ϫ8 and 10 Ϫ7 M), E 2 significantly decreased BCRP protein (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…In the same study, P 4 was observed to be a BCRP inducer, but this effect was detectible only at very high concentrations (Ͼ1 M) (Wang et al, 2006). Circulating estradiol and P 4 concentrations in late pregnancy reach approximately 50 and 500 nM at term, respectively (Batra and Bengtsson 1978;Khan-Dawood and Dawood 1984). Although the free fraction is likely to be much less than this (5-50%, depending on the steroid and gestational age), secretion of these steroids by the placenta is likely to result in increased local concentrations.…”
Section: Regulation Of Placental Abc Transportersmentioning
confidence: 81%
“…Test substances were added as follows: TNF-␣ (20 ng/ml), IL-1␤ (2 ng/ml), IL-6 (20 ng/ml), EGF (10 ng/ml), IGF-II (25 ng/ml), estradiol (100 nM), and P 4 (100 nM). With the exception of TNF-␣, these concentrations were selected to achieve levels that approximate maximal physiological concentrations reported in either peripheral or extracellular fluids (Batra and Bengtsson, 1978;Khan-Dawood and Dawood, 1984;Barreca et al, 1998;Kim et al, 2000;Inada et al, 2001;Lee and Piquette-Miller, 2003). With respect to TNF-␣, because of its potential to induce trophoblast apoptotic death, 20 ng/ml was selected for these studies, representing the maximal concentration that could be used without exerting significant (Ͼ10%) loss of viability (as assessed by MTT assay) over 48 h of treatment.…”
Section: Methodsmentioning
confidence: 99%